EXPLORING SERVICE QUALITY, DIGITAL MARKETING, CONSUMER SATISFACTION AND LOYALTY: A DESCRIPTIVE STUDY - Paquita, Shiva Silvia; Usman, Osly; Adha, Maulana Amirul; Ansar, Rudy (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
The purpose of this study is to determine the level of service quality, digital marketing, consumer satisfaction, and consumer loyalty Shoppe in Jakarta. The research method used in this study is a survey method with the distribution of questionnaires through google forms. The population in this study is consumers who have done online shopping at the Shopee marketplace who live in Jakarta and for the research sample taken as many as 166 respondents, this number was obtained from calculations based on the recommendations of Hair et al. The results of the descriptive analysis of this study showed that the service quality variable had the largest mean value with a score of 3.970 and the lowest value with a score of 3.367. Furthermore, the digital marketing variable has the largest mean value with a score of 3,777 and the lowest value with a score of 3,488. Furthermore, the consumer satisfaction variable has the largest mean value with a score of 3.711 and the lowest value with a score of 3.506. And the consumer loyalty variable has the largest mean value with a score of 3.657 and the lowest value with a score of 3.313.